In-Silico Design of Novel Glucagon-Like Peptide 1 Mutants as Candidate for New Peptide Agonist Drugs - Tony Sumaryada; Ajeng Widya Roslia; Alfi Afifah; Setyanto Tri Wahyudi; Agus Kartono (HAYATI Journal of Biosciences, 2021)
The binding of glucagon-like peptide 1 (GLP-1) incretin hormone and its receptor GLP-1R plays an important role in the human body. The GLP-1 acts as the insulin secretion stimulator through a GLP-1R agonist activation to avoid the type 2 diabetes mellitus problem. A recent development in computational sciences has enabled us to design a new GLP-1 mutant which has a better binding stability to GLP-1R. In this paper, we have conducted an in-depth analysis of protein-protein docking of GLP-1 and GLP-1R receptor to determine the responsible factors affecting the binding stability. The protein-protein binding stability was analyzed by performing the point mutations on the GLP-1 structure and running the molecular dynamics simulation of the docked structures. Five mutants, Lys20Arg, Lys20His, Lys20Ser, Lys20Gly, and Lys20Ala, has been created computationally and docked with GLP-1R and tested via a molecular dynamics simulation and the free energy perturbation calculation to search for the best-binding mutant. Our results have shown that the Lys20His mutant design has the best potential to be developed as a new peptide agonist drug based on its binding affinity and structural integrity as compared to other mutants and the peptide agonist drugs available in the market exenatide, and liraglutide.